Mass Spectrometric Analysis of Exhaled Breath for the Identification of Volatile Organic Compound Biomarkers in Esophageal and Gastric Adenocarcinoma - Kumar, Sacheen; Huang, Juzheng; Abbassi-Ghadi, Nima; Mackenzie, Hugh A; Veselkov, Kirill A; Hoare, Jonathan M; Lovat, Laurence B; Španěl, Patrik; Smith, David; Hanna, George B (Annals of surgery, 2015)
OBJECTIVE: The present study assessed whether exhaled breath analysis using Selected Ion Flow Tube Mass Spectrometry could distinguish esophageal and gastric adenocarcinoma from noncancer controls. BACKGROUND: The majority of patients with upper gastrointestinal cancer present with advanced disease, resulting in poor long-term survival rates. Novel methods are needed to diagnose potentially curable upper gastrointestinal malignancies. METHODS: A Profile-3 Selected Ion Flow Tube Mass Spectrometry instrument was used for analysis of volatile organic compounds (VOCs) within exhaled breath samples. All study participants had undergone upper gastrointestinal endoscopy on the day of breath sampling. Receiver operating characteristic analysis and a diagnostic risk prediction model were used to assess the discriminatory accuracy of the identified VOCs. RESULTS: Exhaled breath samples were analyzed from 81 patients with esophageal (N = 48) or gastric adenocarcinoma (N = 33) and 129 controls including Barrett's metaplasia (N = 16), benign upper gastrointestinal diseases (N = 62), or a normal upper gastrointestinal tract (N = 51). Twelve VOCs-pentanoic acid, hexanoic acid, phenol, methyl phenol, ethyl phenol, butanal, pentanal, hexanal, heptanal, octanal, nonanal, and decanal-were present at significantly higher concentrations (P < 0.05) in the cancer groups than in the noncancer controls. The area under the ROC curve using these significant VOCs to discriminate esophageal and gastric adenocarcinoma from those with normal upper gastrointestinal tracts was 0.97 and 0.98, respectively. The area under the ROC curve for the model and validation subsets of the diagnostic prediction model was 0.92 ± 0.01 and 0.87 ± 0.03, respectively. CONCLUSIONS: Distinct exhaled breath VOC profiles can distinguish patients with esophageal and gastric adenocarcinoma from noncancer controls.
Keywords: senioři; Decision Support Techniques; Stomach Neoplasms; Volatile Organic Compounds; metody pro podporu rozhodování; Male; vydechnutí; Risk Assessment; Middle Aged; ROC Curve; mužské pohlaví; studie případů a kontrol; adenokarcinom; Mass Spectrometry; ROC křivka; Biomarkers, Tumor; ženské pohlaví; nádorové biomarkery; hodnocení rizik; Humans; dechové testy; Breath Tests; Esophageal Neoplasms; lidé středního věku; těkavé organické sloučeniny; Female; Aged; Exhalation; hmotnostní spektrometrie; Adenocarcinoma; nádory jícnu; lidé; Case-Control Studies; nádory žaludku